The Olfactory System Revealed: Non-Invasive Mapping by using Constrained Spherical Deconvolution Tractography in Healthy Humans - Milardi, Demetrio; Cacciola, Alberto; Calamuneri, Alessandro; Ghilardi, Maria F.; Caminiti, Fabrizia; Cascio, Filippo; Andronaco, Veronica; Anastasi, Giuseppe; Mormina, Enricomaria; Arrigo, Alessandro; Bruschetta, Daniele; Quartarone, Angelo (Frontiers in Neuroanatomy, 2017)
Although the olfactory sense has always been considered with less interest than the visual, auditive or somatic senses it does plays a major role in our ordinary life, with important implication in dangerous situations or in social and emotional behaviors. Traditional Diffusion Tensor signal model and related tractography have been used in the past years to reconstruct the cranial nerves, including the olfactory nerve. However, no supplementary information with regard to the pathways of the olfactory network have been provided. Here, by using the more advanced Constrained Spherical Deconvolution diffusion model, we show for the first time in vivo and non-invasively that, in healthy humans, the olfactory system has a widely distributed anatomical network to several cortical regions as well as to many subcortical structures. Although the present study focus on an healthy sample size, a similar approach could be applied in the near future to gain important insights with regard to the early involvement of olfaction in several neurodegenerative disorders.